PENGARUH PENYIMPANAN URINE TERHADAP JUMLAH lEUKOSIT DAN ERITROSIT PADA PENDERITA INFEKSI SALURAN KEMIH DENGAN METODE SY (STANDARD YIELD) - Edy Haryanto; Pestariati .; Anik Handayati; Sri Sulami Endah Astuti (Poltekkes Kemenkes Surabaya, 2015)
Urinary tract infection ( un ) is a pathological condition that is often encountered and marked with urinesediment results indicate nitrite, leucocytes and positive bacteria. In some hospitals, inpatient specimendelivery is often delayed, causing delayed examination. Urine samples should be examined, therefore itis kept at room temperature, lysis of erythrocytes and leukocytes and urine will turn into alkaline. Thisstudy aims to prove how much the influence of the long treatment of urinary tract infection to the numberof leukocytes and erythrocytes urine sediment .